160k views
3 votes
Simplify the expression (2 − 5)(3 + 7) − (4 + 3) and please be sure to explain your steps!

1 Answer

4 votes

Answer: - 37

Explanation:

so (2-5)(3+7) - (4+3) start off by the right side really doesn't matter what side you start on, but I added 4+3=7

x= (2-5)(10) - (7) Then add 3+7=10

x= (-3)(10) - (7) 3rd subtract 2-5=-3

x= -30 - 7 Next multiply -3*10=-30 because two numbers together with parenthesis means multiplication.

x= -37 Lastly subtract -30 - 7 and I got -37

User Viktor Jovanovski
by
4.6k points